Genome-wide identification and characterization of tRNA-derived RNA fragments in land plants - Alves, Cristiane S. [UNESP]; Vicentini, Renato; Duarte, Gustavo T.; Pinoti, Vitor F. [UNESP]; Vincentz, Michel; Nogueira, Fabio T. S. (Springer Nature, 2017)
Key message: The manuscript by Alves et al. entitled “Genome-wide identification and characterization of tRNA-derived RNA fragments in land plants” describes the identification and characterization of tRNAderived sRNA fragments in plants. By combining bioinformatic analysis and genetic and molecular approaches, we show that tRF biogenesis does not rely on canonical microRNA/siRNA processing machinery (i.e., independent of DICER-LIKE proteins). Moreover, we provide evidences that the Arabidopsis S-like Ribonuclease 1 (RNS1) might be involved in the biogenesis of tRFs. Detailed analyses showed that plant tRFs are sorted into different types of ARGONAUTE proteins and that they have potential target candidate genes. Our work advances the understanding of the tRF biology in plants by providing evidences that plant and animal tRFs shared common features and raising the hypothesis that an interplay between tRFs and other sRNAs might be important to fine-tune gene expression and protein biosynthesis in plant cells. Abstract: Small RNA (sRNA) fragments derived from tRNAs (3′-loop, 5′-loop, anti-codon loop), named tRFs, have been reported in several organisms, including humans and plants. Although they may interfere with gene expression, their biogenesis and biological functions in plants remain poorly understood. Here, we capitalized on small RNA sequencing data from distinct species such as Arabidopsis thaliana, Oryza sativa, and Physcomitrella patens to examine the diversity of plant tRFs and provide insight into their properties. In silico analyzes of 19 to 25-nt tRFs derived from 5′ (tRF-5s) and 3′CCA (tRF-3s) tRNA loops in these three evolutionary distant species showed that they are conserved and their abundance did not correlate with the number of genomic copies of the parental tRNAs. Moreover, tRF-5 is the most abundant variant in all three species. In silico and in vivo expression analyses unraveled differential accumulation of tRFs in Arabidopsis tissues/organs, suggesting that they are not byproducts of tRNA degradation. We also verified that the biogenesis of most Arabidopsis 19–25 nt tRF-5s and tRF-3s is not primarily dependent on DICER-LIKE proteins, though they seem to be associated with ARGONAUTE proteins and have few potential targets. Finally, we provide evidence that Arabidopsis ribonuclease RNS1 might be involved in the processing and/or degradation of tRFs. Our data support the notion that an interplay between tRFs and other sRNAs might be important to fine tune gene expression and protein biosynthesis in plant cells.
Keywords: Arabidopsis thaliana; High throughput data; Small RNA; tRF; tRNA-derived RNA fragment